DEVELOPMENT AND EVALUATION OF PROTEIN ENRICHED GUAVA NECTAR BLENDED WITH SOYMILK - G. R. KARANJALKER, D. B. SINGH , V. B. RAJWADE, (The Bioscan, 2013)
Guava nectar blended with soymilk was developed with an aim to produce protein enriched nectar (PEN). The treatments comprising different blends of guava nectar and soymilk were evaluated for physic - chemical and sensory characteristics and shelf life in ambient condition of storage. The study revealed that the guava nectar supplemented with soymilk had increased protein content as much as 2.6% to 5.34% at fresh preparation. The analysis for other parameters like total soluble solids, Titratable acidity, pH, ascorbic acid, reducing sugars, nonreducing and total sugar contents of the product were done at thirty days interval. T. S. S, pH, ascorbic acid, protein and total sugars content of the PEN decreased during storage, while the acidity of the product increased rapidly after 60 days causing the off-odour. As a result, sensory scores decreased after 60 days of storage. The recipe with 70% guava nectar and 30% soymilk recorded highest sensory scores and maximum protein (2.62%) and ascorbic acid (118.9 mg/100g) content.